Edukasi Pentingnya Memulai Investasi di Usia Muda Pada Siswa/Siswi SMP Harapan 2 Medan - Barky, Neneng Yulia; Royani, Ida; Darmansyah, Muthya Rahmi (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This service is carried out with the aim of this community service activity is to educate teenagers who are still in junior high school to know about investment. Investment is an important component of the strategy to usher in a new era by making a commitment to sacrifice a certain amount of money or other types of things at this time in the hope of getting greater rewards in the future. The development and progress of the times requires each generation to continue to adapt and learn, for example about investing. This activity took place at SMP Harapan 2 Medan. The methods used are lecture and discussion/question and answer methods regarding investment. Education regarding the meaning, goals, benefits, impacts and how to invest. After carrying out this activity, the teenage students of SMP Harapan 2 Medan were very satisfied because this activity was able to provide a good understanding of investment and how to make good and safe investments, as well as helping teenagers start learning about investing.